2018
DOI: 10.1107/s2059798318011919
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution crystal structures of the D1 and D2 domains of protein tyrosine phosphatase epsilon for structure-based drug design

Abstract: Here, new crystal structures are presented of the isolated membrane‐proximal D1 and distal D2 domains of protein tyrosine phosphatase epsilon (PTPϵ), a protein tyrosine phosphatase that has been shown to play a positive role in the survival of human breast cancer cells. A triple mutant of the PTPϵ D2 domain (A455N/V457Y/E597D) was also constructed to reconstitute the residues of the PTPϵ D1 catalytic domain that are important for phosphatase activity, resulting in only a slight increase in the phosphatase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…We next attempted to reactivate the PTPRK D2 domain by reintroducing canonical sequences to the WPD loop, PTP signature motif and Q loop (Figure 5—figure supplement 2C; Andersen et al, 2001). Using a pNPP assay, we found no impact of the mutations on D2 domain activity (Figure 5—figure supplement 2D), similar to recent failed attempts to reactivate the PTPRE D2 domain (Lountos et al, 2018). Importantly, the D2 domain mutations did not abrogate binding to several interactors (Figure 5—figure supplement 2E).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…We next attempted to reactivate the PTPRK D2 domain by reintroducing canonical sequences to the WPD loop, PTP signature motif and Q loop (Figure 5—figure supplement 2C; Andersen et al, 2001). Using a pNPP assay, we found no impact of the mutations on D2 domain activity (Figure 5—figure supplement 2D), similar to recent failed attempts to reactivate the PTPRE D2 domain (Lountos et al, 2018). Importantly, the D2 domain mutations did not abrogate binding to several interactors (Figure 5—figure supplement 2E).…”
Section: Resultssupporting
confidence: 84%
“…The corresponding ‘active site’ cysteine residues (C828S for D1 and C1144 for D2) are highlighted in red. ( G ) Surface charge representation of PTPRK-D1 (left; PDB: 2C7S [Eswaran et al, 2006]) and PTPRK-D2 (right; homology model based on PDB: 6D3F (PTPRE-D2; [Lountos et al, 2018])).…”
Section: Resultsmentioning
confidence: 99%
“…26 Like the wedge domains, the D2 domains of RPTPs have controversial functions, but these too have begun to garner interest as potential sites for drug development driven by the recent proliferation of complete crystal structures for RPTP intracellular domains. [27][28][29][30] Historic studies have indicated that the D2 domain may promote 28,31,32 or inhibit 33 the catalytic activity of the D1 domain, may affect substrate specificity, 31 control protein dimerization 32,33 or intra-molecular interactions. 34 It may also have phosphatase or other enzymatic activities such as a denitrase in some contexts.…”
Section: Introductionmentioning
confidence: 99%